Ocorrência de SCCmec tipo IV de Staphylococcus aureus em infecções comunitárias e hospitalares em um hospital universitário de Minas Gerais - Naves, Karinne Spirandelli Carvalho (2011)
Since the first MRSA(Methicillin resistant Staphylococcus aureus) report, this pathogen has spread in hospitals in different regions of the world and is currently regarded as the major nosocomial infections agent, causing benign infections, such as skin and soft tissue and serious, like pneumonia and sepsis. In early 80 s MRSA samples were isolated from community infections in individuals without the presence of risk factors (CA-MRSA - Community-acquired-Methicillin-resistant Staphylococcus aureus). During the last decade there was a CA-MRSA participation in hospital infections increase, especially in the U.S.. This study aimed to investigate CA-MRSA and HAMRSA (Hospital-acquired-Methicillin-resistant Staphylococcus aureus) samples in hospital and community infections, considering classical and molecular epidemiological aspects at the Hospital de Clinicas, Universidade Federal de Uberlândia (HC-UFU), from September 2006 to September 2008. S. aureus cultures were obtained from HCUFU laboratory, and those classified as non-multiresistant were tested for genotypic (Polimerase Chain Reaction, Pulsed Field Gel Electrophoresis e Multilocus Sequence Typing). In total, 206 MRSA samples were selected, with only 45 (21.8%) nonmultiresistant. After genotyping tests eight samples were identified as SCCmec (Staphylococcal Cassete Chromossome mec) IV, belonging to a single clone by PFGE technique, with six pulsotypes. Seven of them were ST (Sequence Typing) 5 (CC5) by MLST. Data indicate a low CA-MRSA prevalence (non MR - 21.8% SCCmecIV - 3.8%) then reported in the United States, isolated from patients with several kind of hospital infections and risk factors. Only one SCCmecIV sample, recovered from a child had community origin, corresponding to an otitis, also characterized as ST5 clone. SCCmecIV samples showed distinct resistance profile and susceptibility to trimethoprim-sulfamethoxazole in all of them. Evolution to death related to multidrug resistant organism infections and skin / soft tissue infection or hospitalization in pediatric units to non-multiresistant infection, were independent risk factors. Hospital mortality was 47.8% among multidrug-resistant MRSA and 26.6% among nonmultidrug- resistant samples. There were no deaths among patients infected with MRSA SCCmecIV. Epidemiological studies of different MRSA strains, in hospital or community, for the medical and hospital relevance, should be cause for public health services concern and additional investigations.